Understanding perceptions of security threats to Australia: the case of refugees and asylum seekers - Bilombele, Asukulu P (Curtin University, 2021)
This thesis presents a critical analysis of alleged security risks posed by refugees and asylum seekers to Australia. Based on relevant literatures and interviews, this thesis reveals that the construction of refugee and asylum seekers as a security threat to Australia is partly driven by a consideration of many factors such as the economy, employment and the scramble for opportunities. However, national security was not the biggest concern of the interviewees during this research.